Dataset: Complex vectorial optics through gradient index lens cascades - He, C; Chang, J; Xi, P; Ma, H; Booth, M; Hu, Q; Wang, J; Antonello, J; He, H; Liu, S; Lin, J; Dai, B; et al. (University of Oxford, 2019)
Source data with full supplementary materials.